Experimental and in silico evaluation of Carthamus tinctorius L. oil emulgel: a promising treatment for bacterial skin infections - Saeed, Javaria; Hussain Shah, Syed Nisar; Javed, Hina; Aslam, Asma; Ali, Anam; Siddique, Farhan; Zahra, Tahreem; Bin Jardan, Yousef A.; Wondmie, Gezahign Fentahun; Nafidi, Hiba-Allah; Bourhia, Mohammed (Frontiers in Cellular and Infection Microbiology, 2023)
The current study aimed to develop a topical herbal emulgel containing Carthamus tinctorius L oil (CT) extract which has been scientifically proven for its anti-bacterial and antioxidant activity for the ailment of bacterial skin infections.The CT-emulgel was formulated by RSM methodology and was evaluated by various parameters like extrudability, spreadability, pH, viscosity, and anti-bacterial and anti-oxidant activity. Molecular docking was also done by using AutoDOCK.Results: Among all formulated CT-emulgels, F9 and F8 were optimized. Optimized formulations have shown good spreadability and extrudability characteristics. Sample F8 has a % inhibition of 42.131 ± 0.335, 56.720 ± 0.222, and 72.440 ± 0.335 at different concentrations and Sample F9 has a % inhibition of 26.312 ± 0.280, 32.461 ± 0.328 and 42.762 ± 0.398 at a concentration of 250, 500 and 1000µg/ml which shows that both samples F8 and F9 have significant anti-oxidant potential. Optimized CT-emulgels F8 and F9 have significant anti-bacterial activity against Staphylococcus aureus and Escherichia coli as p-value = 0.00 and diameter of % inhibition varies from 4.0 mm to 15.0 mm. The comparative investigation through molecular docking binding affinities and interactions of ligands with various target proteins provides insights into the molecular processes behind ligand binding and may have significance for drug discovery and design for the current study.The current study suggests that Carthamus tinctorius L-based emulgel has good antioxidant and anti-bacterial activity against Escherichia coli for the treatment of bacterial skin infections.